Experience With Hydroxychloroquine and Azithromycin in the Coronavirus Disease 2019 Pandemic: Implications for QT Interval Monitoring. Issue 12 (16th June 2020) - Ramireddy, Archana; Chugh, Harpriya; Reinier, Kyndaron; Ebinger, Joseph; Park, Eunice; Thompson, Michael; Cingolani, Eugenio; Cheng, Susan; Marban, Eduardo; Albert, Christine M.; Chugh, Sumeet S.
Abstract : Background: Despite a lack of clinical evidence, hydroxychloroquine and azithromycin are being administered widely to patients with verified or suspected coronavirus disease 2019 (COVID‐19). Both drugs may increase risk of lethal arrhythmias associated with QT interval prolongation. Methods and Results: We analyzed a case series of COVID‐19–positive/suspected patients admitted between February 1, 2020, and April 4, 2020, who were treated with azithromycin, hydroxychloroquine, or a combination of both drugs. We evaluated baseline and postmedication QT interval (corrected QT interval [QTc]; Bazett) using 12‐lead ECGs. Critical QTc prolongation was defined as follows: (1) maximum QTc ≥500 ms (if QRS <120 ms) or QTc ≥550 ms (if QRS ≥120 ms) and (2) QTc increase of ≥60 ms. Tisdale score and Elixhauser comorbidity index were calculated. Of 490 COVID‐19–positive/suspected patients, 314 (64%) received either/both drugs and 98 (73 COVID‐19 positive and 25 suspected) met study criteria (age, 62±17 years; 61% men). Azithromycin was prescribed in 28%, hydroxychloroquine in 10%, and both in 62%. Baseline mean QTc was 448±29 ms and increased to 459±36 ms ( P =0.005) with medications. Significant prolongation was observed only in men (18±43 ms versus −0.2±28 ms in women; P =0.02). A total of 12% of patients reached critical QTc prolongation. Changes in QTc were highest with the combination compared with either drug, with much greater prolongation with combination versus azithromycin (17±39 ms versus 0.5±40 ms; P =0.07). No patients manifested torsades de pointes. Conclusions: Overall, 12% of patients manifested critical QTc prolongation, and the combination caused greater prolongation than either drug alone. The balance between uncertain benefit and potential risk when treating COVID‐19 patients should be carefully assessed.